Human error impact in structural safety of a reinforced concrete bridge - Pereira, Neryvaldo Jesus Galvão (2022)
The economic and social losses due to increasing bridges collapse over the years have underlined the importance of the development of more robust bridge structural systems when exposed to harmful events, such as natural hazards, human-made hazards and human errors. Natural and human-made hazards are usually explicitly addressed in the numerous works available in the literature, but when it comes to human errors, very few studies can be found. It is worth mentioning that human errors have been identified as one of the main causes of bridges failure. Consequently, the main goal of this paper is the assessment of human errors impact on the robustness and safety of a prestressed reinforced concrete bridge through a probabilistic-based approach. Uncertainties concerning the numerical model, material strength, geometry and loading condition are used as key input parameters for the probabilistic assessment. Considering the structural system performance in its early days (i.e., virgin reliability index) the human error impact in structural safety is measured according to the structural system performance reduction given different errors with different magnitudes. Therefore, the structural system ability to maintain acceptable levels of performance, given such errors, is assessed.